Empowering Guidance Studios to Enhance the Quality of Education for Migrant Children with Learning Monitoring System - Azhari, Imam; Purwanti, Siwi; Handayaningsih, Sri; Maranti, Safika (Journal of Community Practice and Social Welfare, 2024)
This community service activity responds to issues in Non-Formal Education (NFE) supervised by the Embassy of the Republic of Indonesia (KBRI) in Kuala Lumpur. The issues involve: (1) existing curriculum in Guidance Studios, but reliance on inconsistent volunteer instructors is a barrier, and (2) volunteers' lack of understanding of teaching methods and specific policies related to the teaching process in the studios. The objective of this community service activity is to strengthen the capacity of managers to develop work programs and enhance the Learning Studio curriculum with support from a computer-based learning monitoring system. The method involves discussions and training as the basis for developing a system designed to support an appropriate monitoring model, with a user-centered design approach. The outcome of this activity is a prototype monitoring model using mobile devices, enabling instructors at the Guidance Studios and the Local Employment Information System (SIKL) to monitor ongoing learning processes.